Cover Feature: Photosensitised Multiheme Cytochromes as Light‐Driven Molecular Wires and Resistors (ChemBioChem 20/2018). (2nd October 2018) - van Wonderen, Jessica H.; Li, Daobo; Piper, Samuel E. H.; Lau, Cheuk Y.; Jenner, Leon P.; Hall, Christopher R.; Clarke, Thomas A.; Watmough, Nicholas J.; Butt, Julea N.
Abstract : The cover feature picture shows a chain of four close‐packed hemes in a cytochrome labelled with a Ru II phototrigger of electron injection into the heme chain. The behaviours of five such Ru II ‐labelled cytochromes were studied during irradiation by visible light in the presence of a sacrificial electron donor. The electrical properties of these biohybrids were defined by the site of electron injection, a finding that paves the way for the rational use of photosensitised multiheme cytochromes as components of light‐driven, light‐responsive or light‐harvesting molecules and materials. More information can be found in the full paper by J. N. Butt et al. onpage 2206 in Issue 20, 2018 (DOI:10.1002/cbic.201800313 ).